Searching For Information Quality of Financial Statements: From the Main Principles Up To Neuroaccounting - Guptor, Marina; Rudžionienė, Kristina (Buhalterinės apskaitos teorija ir praktika, 2018)
[only abstract in English; full article and abstract in Lithuanian]The aim of the article is to study the relationship between neuroscience and financial accounting, the fundamental aspects of decision-making and decision-making by accounting specialists from the perspective of neuroscience. Methods: conceptual, critical, systematic analysis of scientific literature, comparison and generalization.Properly grouped and presented information in the financial statements conveys a clear and understandable picture about an entity that has to reduce the level of entropy (uncertainty) of its users. The financial statements are prepared by accounting specialists, and it is therefore important that they, when preparing their reports, would replicate the details of economic events and economic facts as accurately the information of reports.Scientific literature does not have a common definition of the “quality of accounting information”, but the concept of the quality of financial statements can be considered in the context of their normative regulation. In this case, compliance with the basic accounting principles in the preparation of financial statements must ensure the quality of the reports. The results of the research carried out in Lithuania revealed that the overall average of the financial statements is 50-59%. The quality of financial reports is influenced by not only compliance with the general principles, but also the human factor.Neuroaccounting - the subcategory of neuroscience - is a new trend in the modern behavioural accounting based on the research of the activity of neurons involved in the human decision-making process. Neuroaccounting is a new way for scientific evaluation of accounting, and research results are important both for investors who analyse financial statements, for auditors who perform audit tasks, and for accountants, who record business events, analyse and reflect transactions, formation of budget and perform other accounting tasks. Neuroscience research methods can also be valuable in conducting research and determining how the brain of accounting specialists can resolve conflicts arising from the adoption of one or another decisions related to the presentation of economic transactions in accounting, their assessment as well as presentation of information about them in financial statements.